Business Capital Funding Through the Financial Sector to Reduce Unemployment in Indonesia - Bagus Kusuma; Ainnatul Muthmainnah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan)
This research aimed to study the role of the financial sector and foreign investment in increasing domestic production output. Where the increase in production output will increase the factors of production, one of which is labor. The data used in this study are annual time series data from the 2004 to 2021, and this study employed the Error Correction Model (ECM) approach to estimate the short-term effect and OLS to determine the long-term effect. The results showed that funding growth through the financial sector to the industrial sector in Indonesia has grown consistently since 2004 which has continued to encourage improved economic performance after the 1998 crisis. There is also a relationship between financial variables and fiscal policy on unemployment in both the short and long term. There are several ways to deal with unemployment both in the long term and in the short term, such as when an economic slowdown occurs. By increasing FDI, bank credit and funding in the the capital market, the private sector can continue to expand its business. This private expansion phase will increase the output of goods or services. With the increase in production output, employment will continue to be positive.